Evaluation of Programs in Education and Administration: Ideas for a Project of Improvement to the Model of Kirkpatrick - Marcos Antonio Martins Lima (Universidad Autónoma de Madrid, 2018)
The present article approaches the evaluation of education programs in educations organizations, schools and managerials, through a methodological strategy structured in four areas: the philosophy of science area, the theoretical area, the morphological area and the technical area (De Bruyne, et. al., 1977). The thoughts of Gaston Bachelard and the structural-systemic approach fill the theoretical and philosophy of science fields. In these methodological axes, wide investigation of phenomenon evaluation in the fields of education and administration has been carried out. The term organizational education is used in the new managerial context and attending to the demands of technological innovations and better competitiveness. Several evaluation models in education and managerial education programs are presented and analyzed in the morphological area by authors from Brazil and the United States. The Kirkpatrick model which appeared in 1959 is taken as a reference after the verification, in exploratory and applied research of its use in large companies based in Brazil. The improvement project for the Kirkpatrick model is based on the concepts of procedural evaluation, evaluation based on the dialogue, evaluation contract and quantitative and qualitative use indicators.